Stem cell origins of leukaemia and curability. - Greaves, M. F. (Nature Publishing Group, 1993)
It is suggested that most childhood acute lymphoblastic leukaemias and some other paediatric cancers are chemo-curable because they arise in stem cell populations that are functionally transient, chemosensitive and programmed for apoptosis. Most adult acute leukaemias are chemo-incurable at least in part because they originate in relatively drug resistant stem cells with extensive self-renewal capacity. The latter property in turn increases the probability of clones evolving with multi-drug resistance. Particular mutations may superimpose additional adverse features on leukaemic cells.